Research insights : a handbook on grant writing and program management - Tayal, Rajiv K; Role of science administration (New Delhi : Atlantic, 2023)
The book provides necessary insights into various nuances of grant writing as well as management of R&D programs, based on author$1 (Bs observations and experiences during the course of his professional engagements over the last three decades. It studies the management of research programs$1 (Bcomprising evaluation of research proposals, decisions on grant making, and subsequent servicing of funded proposal. It emphasizes on the need to do something to raise the quality of research and the grant proposals which are received for funding; and also, on the need to be more innovative, thoughtful, and diligent in the management of research programs to fulfill the individual aspirations and national agenda. The book has been organized in two parts. The first part is on (3z(Bgrant writing, defense, and implementation(3y (Band covers scientific research and development, research and academics, funding for research, evaluation and funding of research grants, writing a research grant, defending a research grant, and frequently asked questions related to the topics. The second part is on (3z(Bmanagement of research programs(3y (Band covers function of science administration, evaluation of grant proposals, peer review, personal presentation, expert committees, grant making, special programs, and the final word incorporating role of program officer, speed of delivery, participation and ownership, and striving for excellence.s
Includes bibliographical references (p. 178-182) and index.
Keywords: Grant writing strategies; Research proposal evaluation and funding; Research program management; Improving research quality